Substance Abuse among Students of Zanjan’s Universities (Iran): A Knot of Today's Society - Abolfazl Goreishi; Zahra Shajari (Addiction and Health, 2013)
Background: In order to assess the status of drug abuse and likely addiction among university students, a descriptive study was designed. Methods: 1200 subjects among the students of three universities in Zanjan were selected by stratified random sampling and their demographic information and history of substance abuse including hookah, cigarette, codeine, ibuprofen, alcohol, diazepam, tramadol, cannabis, opium, grass, heroin, crack, X pill, morphine, marijuana, Librium, and LSD were assessed by a standard questionnaire and were analyzed in 2010. Findings: The mean age of students was 21.3 ± 2.3 years (ranged 18-38 years) and the mean age of drug abuse onset was 19.45 years old. 48.2% of male students and 23.4% of female had a history of drug abuse at least once. 6.3% of males and 1.2% of female subjects were addicted constantly which the difference was statically significant (P < 0.001). 32.7% were motivated by pain and 13.3% seeking for pleasure. Hookah with 18% and LSD with 1% had the lowest and highest percentage of drug use, respectively. Conclusion: Substance abuse was higher in males than females. Drug abuse was higher among older students with higher degree, and with psychological disorder history. It seems that we require goal directed programs to control and reduce the prevalence of substance abuse, raise students’ awareness and increase students’ information about substance disadvantages especially in their entrance. Keyword: Substance abuse, Addiction, University students